Arrhythmias and COVID-19: A review (2020)
Current understanding of the impact of COVID-19 on arrhythmias continues to evolve as new data emerges. Cardiac arrhythmias are more common in critically ill COVID-19 patients. The potential mechanisms that could result in arrhythmogenesis among COVID-19 patients includes hypoxia caused by direct viral tissue involvement of lungs, myocarditis, abnormal host immune response, myocardial ischemia, myocardial strain, electrolyte derangements, intravascular volume imbalances and drug sides effects. To manage these arrhythmias, it is imperative to increase the awareness of potential drug-drug interactions, to monitor QTc prolongation while receiving COVID therapy and provide special considerations for patients with inherited arrhythmia syndromes. It is also crucial to minimize exposure to COVID-19 infection by stratifying the need for intervention and using telemedicine. As COVID-19 infection continues to prevail with a potential for future surges, more data is required to better understand pathophysiology and to validate management strategies. Keywords: COVID-19, SARS-CoV-2, Arrhythmias, QT prolongation, Torsades De Pointes, Channelopathies